Stress shifts the response of the bed nucleus of the stria terminalis to an anxiogenic mode - Silva, Ana Paula Ventura (2012)
The bed nucleus of the stria terminalis (BNST) is critically implicated in anxiety behavior and control of the hypothalamus–pituitary–adrenal axis. Having previously shown that chronic stress triggers dendritic/synaptic remodeling in specific nuclei of the BNST, we characterised the pattern of activation of neurons within different regions of the BNST under basal conditions and after an anxiogenic stimulus in control and stressed rats. Under basal conditions, stressed, but not control, animals displayed increased cFOS expression in the dorsomedial nucleus and decreased activation of the principal nucleus. This pattern resembled that observed in controls that had been exposed to the anxiogenic stimulus. Subsequent analysis of various BNST subnuclei revealed differential patterns of gene expression in controls and stressed animals. We found decreased levels of corticotropin-releasing hormone 1 receptor mRNA expression in the dorsomedial and fusiform nuclei, and a global increase in the levels of corticotropin-releasing hormone 2 receptor in the principal nucleus. In addition, we found subnuclei-specific increases in GABAA and NR2B receptors in stressed animals, which suggest changes in the GABAergic and glutamergic innervation of the BNST. Importantly, these findings were associated with increased anxiety-like behavior and impaired control of the hypothalamus–pituitary–adrenal axis in stressed animals. In summary, these data reveal that chronic stress shifts the pattern of response of the BNST to an anxiogenic mode and provide new information on the underlying mechanisms of the stress-induced hypercorticalism and hyperanxious status.